Leadership development impact evaluation approaches - Mbatha, Vuyile Cynthia (My University, 2022)
This mixed methods multiple case study research investigated the approaches used in the impact evaluation of leadership development initiatives within the context of financial services corporate organisations operating in the African continent and headquartered in South Africa. Organisations around the world are continuously investing incremental amounts of money into learning and development, more specifically directed towards leadership development initiatives (Boyett & Boyett, 1998; Clark & Clark, 1994; McCauley, Moxley, & Van Velsor, 1998) and yet to date, research and literature on leadership has been predominately focused on theories and approaches to leadership (Bass & Stogdill, 1990; Boyett & Boyett, 1998; Brungardt, 1996; Gardner, 1990; Jackson, 1992; Northouse, 1997; Yukl & van Fleet, 1992) with limited research focused on demonstrating the holist impact of leadership development investments (Avolio, 2007). Although research has been done on evaluation practices in relation to training and development, few researchers have addressed the matter of impact evaluation specifically for leadership development, through case study research using the mixed methods lenses. This research study was aimed at investigating the approaches used to measure the impact of leadership development initiatives, through engaging with stakeholders that have a vested interest in leadership development. The qualitative results revealed that the current leadership development evaluation approaches are a case of a self-fulfilling prophecy, enabled by the unilateral design of the current evaluation approaches and matrices for evaluation are not agreed upfront with relevant key stakeholders. Furthermore, the current approaches do not measure leadership impact holistically. This is problematic as business stakeholders ii are not able to obtain a sense of the true and holistic impact of leadership development initiatives, in relation to their context and matrices that are important for them as business stakeholders are not included. The quantitative findings highlight the importance of having a leadership development evaluation approach that is 1) credible; 2) simple; 3) enables the evaluation to be done across all three levels of the triple bottom line; and an approach that is 4) theoretically sound. The results provided insights into the core elements that should be included in evaluating leadership development impact holistically and through this theory emerged which informs the theoretical contribution in this research study. In this, a proposed holistic leadership development impact evaluation approach is presented as an evaluation framework with underlying principles used to explain what informs the framework and how the framework may be applied in the evaluation of leadership development initiatives within the context of corporate leadership in South
A thesis submitted in fulfilment of the requirement for the degree Doctor of Philosophy in Business Management & Leadership to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Leader; Leadership; Learning; Learning & Development; Leadership Development; Evaluation; UCTD; SDG-8: Decent work and economic growth